Bakuchiol is an effective antimicrobial agent in maintaining oral health of the elderly adults - Razak, Fathilah Abdul; Gunasegar, Shan; Bakri, Marina Mohd; Ab-Murat, N.; Ramathan, Anand; Hossain, Mohammad Zakir (2018)
Aging leads to hyposalivation, which in turn alters the normal oral microflora. Candida species often becomes a predominant inhabitant due to changes in the physiology and functions of the oral fluid and tissues. This study aimed to determine the antimicrobial activity of active compound bakuchiol on candidal population of the elderly adults. The action mechanism of bakuchiol may suggest its potential as an effective agent for the maintenance of oral health in this target group.